The European Arrest Warrant: some pragmatic and translation aspects - Dolores Ross; Marella Magris (JoSTrans: The Journal of Specialised Translation)
The European Arrest Warrant (EAW) is an important legal instrument of judicial cooperation and mutual assistance in criminal matters within the European Union. Translation quality and functionality is therefore a fundamental issue in this field, as we argue in the present article. After a brief introduction to the EAW, we have performed a genre-based analysis of Belgian Dutch and Italian EAWs, addressing terminological issues, morphosyntactic questions and discursive strategies. Subsequently we have taken into consideration the pragmatic dimension, focusing especially on the participants in the very particular discourse situation presented by EAWs. Finally we have discussed the translator's role and competence. The EAW is a normative text issued by a EU Member State with a view to arrest and surrender a requested person by another Member State. The translation of an EAW is considered a parallel legal text, because in the target judicial system it performs the function of the judicial decision in the source system. Against this background the quality of translation services, the translator's tasks and the issue of national registers for translators are essential elements, also in the light of increasingly important considerations such as the commitment to fundamental rights.